Logical valuation of connectives for fuzzy control by partial differential equations - Berger, Michael; Schwarz, Helmut (Zielona Góra: Uniwersytet Zielonogórski)
There exist numerous criteria (axiomatic, progmatic and empirical) to choose from the fuzzy connectives and apply them to an intersection (conjunction) and union (disjunction). So far these valuations have had no direct connection between the fuzzy logic and the control for technical processes. In this paper, a new valuation (logical valuation) of fuzzy connectives is proposed.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka